Search for single production of vector-like quarks decaying to a Z boson and a top or a bottom quark in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (Journal of High Energy Physics, 2017)
A search for single production of vector-like quarks, T and B, decaying into aZ boson and a top or a bottom quark, respectively, is presented. The search is performedusing data collected by the CMS experiment at the LHC in proton-proton collisions atps= 13 TeV, corresponding to an integrated luminosity of 2.3 fb